First ornithopod remains from the Bajo de la Carpa Formation (Santonian, Upper Cretaceous), northern Patagonia, Argentina - Cruzado Caballero, Penélope (2018)
In the last decades, the Argentinian ornithopod record has been increased with new and diverse bone remains found along all the Upper Cretaceous. Most of them are very incomplete and represent taxa of different size. As result, the studies about the palaeobiodiversity of the Ornithopoda clade in South America are complex. In this paper, new postcranial remains of an indeterminate medium-sized ornithopod from the Santonian Bajo de la Carpa Formation (Rincón de los Sauces, Neuquén province) are presented. They present diagnostic features of the Ornithopoda clade, and several characters that relate them with other Argentinian ornithopods, especially with the medium-sized members of the Elasmaria clade sensu Calvo et al. (2007) (Macrogryphosaurus and Talenkauen). The postcranial material allows to identificate at least three different ontogenetic stages: adult, subadult more immature and subadult. These bones are the first record of Ornithopoda for the Bajo de la Carpa Formation and one of the very scarce Santonian records of this clade in South America. The diversity of the Late Cretaceous South American ornithopods presents two clear distributions: the Cenomanian-Santonian was characterized by small and medium euiguanodonts and elasmarian; and the Campanian–Maastrichtian by the medium sized elasmarian and large sized hadrosaurids.